Wafer‐Scale Epitaxial Growth of Two‐dimensional Organic Semiconductor Single Crystals toward High‐Performance Transistors - Wang, Jinwen; Ren, Zheng; Pan, Jing; Wu, Xiaofeng; Jie, Jiansheng; Zhang, Xiaohong; Zhang, Xiujuan (Advanced materials (Weinheim), 2023)
The success of state‐of‐the‐art electronics and optoelectronics relies heavily on the capability to fabricate semiconductor single‐crystal wafers. However, the conventional epitaxial growth strategy for inorganic wafers is invalid for growing organic semiconductor single crystals due to the lack of lattice‐matched epitaxial substrates and intricate nucleation behaviors, severely impeding the advancement of organic single‐crystal electronics. Here, an anchored crystal‐seed epitaxial growth method for wafer‐scale growth of 2D organic semiconductor single crystals is developed for the first time. The crystal seed is firmly anchored on the viscous liquid surface, ensuring the steady epitaxial growth of organic single crystals from the crystal seed. The atomically flat liquid surface effectively eliminates the disturbance from substrate defects and greatly enhances the 2D growth of organic crystals. Using this approach, a wafer‐scale few‐layer bis(triethylsilythynyl)‐anthradithphene (Dif‐TES‐ADT) single crystal is formed, yielding a breakthrough for organic field‐effect transistors with a high reliable mobility up to 8.6 cm2 V−1 s−1 and an ultralow mobility variable coefficient of 8.9%. This work opens a new avenue to fabricate organic single‐crystal wafers for high‐performance organic electronics. An anchored crystal‐seed epitaxial growth method is developed to effectively suppress the multiple nucleation behavior of the molecules and enhance the 2D growth of organic crystals. In consequence, wafer‐scale few‐layer organic single crystals are successfully fabricated on the viscous liquid substrate. Organic field‐effect transistors based on the crystal exhibit high device performance with excellent uniformity.